Kesehatan dan Perobatan dalam Tradisi Islam: Kajian Kitab Shahih Al-Bukhârî. - Nurhayati Nurhayati (Universitas Islam Negeri Jakarta, 2016)
Health and Medicine Treatment in Islamic Tradition: a Study on Sahîh al-Bukhârî. The main objective of medical treatment in Islam is to maintain health rather than curing the disease. This article specifically discusses the views of Imam Bukhari on health coverage and medicine treatment in Islam as stated in his book, Sahih al- Bukhari. Sahih al-Bukhari is one of the most important and authentic collection books of Hadith. The description of health and medicine in Saheeh al-Bukhari discussed in the chapter of al-Tibb. The Hadiths collected in the book are more associated with the prevention treatment (preventive medicine) rather than the healing treatment (therapeutic medicine).DOI: 10.15408/ajis.v16i2.4452